2020
DOI: 10.1016/j.jinf.2020.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Serial simultaneously self-swabbed samples from multiple sites show similarly decreasing SARS-CoV-2 loads in COVID-19 cases of differing clinical severity

Abstract: Serial simultaneously self-swabbed samples from multiple sites show similarly decreasing SARS-CoV-2 loads in COVID-19 cases of differing clinical severity Detection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is essential for diagnosis of Coronavirus disease (COVID-19). Nasopharyngeal swabs (NPS) are recommended by the World Health Organisation (WHO) as the current standard method to detect SARS-CoV-2 in suspected patients. 1 However, collection of an NPS or oropharyngeal swab (OPS) can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…However, critically ill adults or children are often unable to spontaneously produce sufficient amounts of saliva or sputum [10]. Findings of previous studies concerned with detection of SARS-CoV-2 in saliva specimens were limited by small sample size and diverse methodology [11][12][13][14]. Whether PCR from saliva mouthwash is an accurate method to detect SARS-CoV-2 in symptomatic patients remains, therefore, yet to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…However, critically ill adults or children are often unable to spontaneously produce sufficient amounts of saliva or sputum [10]. Findings of previous studies concerned with detection of SARS-CoV-2 in saliva specimens were limited by small sample size and diverse methodology [11][12][13][14]. Whether PCR from saliva mouthwash is an accurate method to detect SARS-CoV-2 in symptomatic patients remains, therefore, yet to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Another study, which we could not include into our systematic review due to a limited number of examined patients, was conducted by Pan et al and investigated the diagnostic performance of self-collected OPS, nares, cheek, and conjunctiva swabs in three patients with different severities of COVID-19. They found that a self-obtained nares swab as well as self-collected conjunctiva, cheek, or OPS samples were able to detect SARS-CoV-2 in the early stage of disease and showed that Ct values increased over time (56) .…”
Section: Mcculloch Et Al As Well As Tu Et Al Reported High Sensitivities Of Mts Relative To Nps and A High Correlation Of Their Respectivmentioning
confidence: 99%